2021
DOI: 10.3390/ma14143970
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ion Milling for Surface Preparation for EBSD Analysis

Abstract: An electron backscattered diffraction (EBSD) method provides information about the crystallographic structure of materials. However, a surface subjected to analysis needs to be well-prepared. This usually requires following a time-consuming procedure of mechanical polishing. The alternative methods of surface preparation for EBSD are performed via electropolishing or focus ion beam (FIB). In the present study, plasma etching using a glow discharge optical emission spectrometer (GD-OES) was applied for surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In previous investigations related to plasma sterilization [9,39], they demonstrated that continuous pumping in the vacuum chamber could remove by-products without re-contamination. The high-energy electron beam in a high vacuum system can be suitable for ion beam etching or doping processes [40]. Based on the results of this study, the vacuum plasma treatment can be effectively used as a surface nitriding technique through high-energy ion bombardment.…”
Section: Discussionmentioning
confidence: 91%
“…In previous investigations related to plasma sterilization [9,39], they demonstrated that continuous pumping in the vacuum chamber could remove by-products without re-contamination. The high-energy electron beam in a high vacuum system can be suitable for ion beam etching or doping processes [40]. Based on the results of this study, the vacuum plasma treatment can be effectively used as a surface nitriding technique through high-energy ion bombardment.…”
Section: Discussionmentioning
confidence: 91%
“…Although being widely used, characterization of a material's texture via EBSD does pose some challenges. On the one hand, the requirement of a flat surface to maximize the backscatter yield makes sample preparation time-consuming and leads to a danger of introducing extra deformation in the near-surface region 9 . On the other hand, the field of view studied in EBSD is typically limited to a few square millimeters (and, often, significantly less than that) which makes it difficult to collect sufficient data to fully characterize a material's texture.…”
Section: Introductionmentioning
confidence: 99%